Moderately-high humoral antibody responses to a H5N2 inactivated vaccine did not suppress shedding of highly pathogenic H5N1 Avian Influenza virus during challenge - Syed Hassan, Sharifah; K., Hasuzana; M. Noor, Suriani; Mohamed, Maizan; Ong, G. H.; D., Azizah; Omar, Abdul Rahman; Ideris, Aini (Veterinary Association Malaysia, 2013)
Twelve SPF chickens with moderately high-titred HI antibodies of 7 log2 and 8 log2achieved at week 4 post-vaccination after a single vaccination with an inactivated whole-H5N2 virus vaccine developed at Veterinary Research Institute, Ipoh were selected for efficacy and shedding studies. The H5N2 vaccine virus shares approximately 88.2% homology to the HA gene of the H5N1 challenge virus. The chickens with moderately high titred-HI humoral antibodies provided 100% protection against mortality and morbidity after challenged with a lethal highly pathogenic H5N1 Malaysian strain. The challenge H5N1 virus was reisolated from pooled cloacal swabs of chickens with HI titres of 7 log2 and 8 log2 at 3 days post challenged, however, was not reisolated from the pooled oropharyngeal swabs. The virus titre at reisolation was 101EID50/0.1 ml in pooled cloacal samples from both the 7 log2 and 8 log2 HI titred-chickens. There was no challenge H5N1 virus reisolated from chickens with HI titre of 9 log2. This study demonstrated that chickens with moderately high HI humoral antibodies protect chickens against clinical disease and mortality did not fully prevent infection, however, was able to reduce virus shed via the cloaca and oropharynx.